Mortality Of Malignant Melanoma In Central Serbia, In The Period 1999-2015 - Milica Pantovic; Ognjen Djordjevic; Svetlana Radevic; Dragic Bankovic; Katarina Parezanovic Ilic; Snezana Radovanovic (Mattioli1885, 2023)
Introduction: Malignant melanoma is one of the rarest but the most deadly form of skin cancer. Objective: The objective of this paper was to analyze the epidemiological characteristics and trends of mortality from malignant melanoma of the population of Central Serbia in the period 1999-2015. Methods:  The study was designed as a retrospective descriptive epidemiological study. Standardized mortality rates were used in statistical data processing.  A linear trend model and regression analysis were used to examine trends in malignant melanoma mortality. Results:  In Serbia, malignant melanoma mortality shows an increasing trend. The overall age-adjusted melanoma death rate was 2.6 per 100 000 with a higher death rate among men (3.03per 100 000) than among women (2.1 per 100 000). Malignant melanoma mortality rates increase with age in both sexes and are highest in the age group of 75 and older. The highest increase in mortality in men is recorded in the age group of 65-69 years, with an average percentage increase of 21.33 (95% CI, 8.40 - 51.05), while in women the largest increase in mortality was recorded in the age group 35-39 years, with an average percentage increase of 31.4  and in the age group of 70-74 years, 12.9 . Conclusions: The trend of increasing mortality from malignant melanoma in Serbia is similar to those in most developed countries. Education and improvement of the awareness of the general population and among health professionals remain vital to reducing melanoma mortality in the future.